The combination of implanting with Revalor-200 and feeding Zilmax increases ribeye area of fed cows - Neill, S.; Marston, T.T.; Higgins, James J.; Unruh, John A.; Jaeger, John R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Mature cows are typically removed from the cow herd for various reasons, such as reproductive inefficiency and poor performance. It has been estimated that as much as 15 to 25% of a ranch’s revenue may be from cull cows. When cows are culled from the herd, they are normally in thin condition and potentially can be fed to gain weight and increase income. Previous studies indicate that feeding a high-energy diet and implanting cull cows can improve performance and increase meat yield. Zilmax (zilpaterol hydrochloride; Intervet Inc., Millsboro, DE) is a β-adrenergic agonist approved as a growth promotant in feedlot cattle for use during the last 20 to 40 days prior to harvest. β-agonists repartition nutrients away from fat deposition and toward protein deposition. Studies in young animals have shown β-agonists to improve performance and carcass cutability characteristics. However, few studies using β-agonists in cull cows have been conducted. Therefore, the objective of this study was to determine the effects of concentrate feeding, implanting, and feeding Zilmax on performance and carcass characteristics of cull cows fed for 70 days.
Keywords: Beef; Cattle; Zilmax; Revalor-200; Ribeye